A place for us eaudiobook A novel. - Mirza, Fatima Farheen (Random House Audio, 2018)
AN INSTANT NEW YORK TIMES BESTSELLER • NATIONAL BOOK AWARD “5 UNDER 35” NOMINEE • NEW YORK’S “ONE BOOK, ONE NEW YORK” PICK Named One of the Best Books of the Year: Washington Post • NPR • People • Refinery29 • Parade • BuzzFeed “Mirza writes with a mercy that encompasses all things.” — Ron Charles, Washington Post   Hailed as “a book for our times” (Christiane Amanpour), A Place for Us is a deeply moving and resonant story of love, identity, and belonging. As an Indian wedding gathers a family back together, parents Rafiq and Layla must reckon with the choices their children have made. There is Hadia: their headstrong, eldest daughter, whose marriage is a match of love and not tradition. Huda, the middle child, determined to follow in her sister’s footsteps. And lastly, their estranged son, Amar, who returns to the family fold for the first time in three years to take his place as brother of the bride. What secrets and betrayals have caused this close-knit family to fracture? Can Amar find his way back to the people who know and love him best? A Place for Us takes us back to the beginning of this family’s life: from the bonds that bring them together, to the differences that pull them apart. All the joy and struggle of family life is here, from Rafiq and Layla’s own arrival in America from India, to the years in which their children—each in their own way—tread between two cultures, seeking to find their place in the world, as well as a path home. A Place for Us is a book for our times: an astonishingly tender-hearted novel of identity and belonging, and a resonant portrait of what it means to be an American family today. It announces Fatima Farheen Mirza as a major new literary talent.